Mammals and Bird Conservation Strategies Through Community-Based Wildlife Watching Ecotourism Development in Perhutani Area, Poncokusumo, Malang District, East Java - Ika Yuni Agustin; Luchman Hakim; Amin Setyo Leksono (Biotropika: Journal of Tropical Biology, 2023)
Perhutani area in Poncokusumo is inhabited by endemic and protected mammals and birds. However, the data on the species are still lacking while the wildlife is threatened by forest conversion and hunting activities. The objectives included identifying mammals and birds species in the Perhutani area in Poncokusumo, describing the local people and visitor's perception of the idea of developing wildlife-watching ecotourism and developing a strategy for mammals and birds conservation through wildlife-watching ecotourism based on the local community. A field survey was done through direct observation and species recognition through morphological characteristics. Interviews were conducted in community lives in Poncokusumo village. The results showed that the Perhutani forest in Poncokusumo has 13 species of mammals and 54 species of birds and is included in the category with very good quality fauna diversity. Local people and visitors' perceptions of mammals and birds vary, but most respondents support developing wildlife-watching ecotourism. From the SWOT analysis, crucial optional strategy are includes increasing opportunities and strengths factors to minimize weaknesses. Some weakness of tourism development was found related to the threats and weaknesses, including hunting rate, habitat degradation and local community knowledge and awareness to support conservation program. This suggested that involving the local community in the tourism industry was crucial. Mammals and bird conservation through wildlife watching ecotourism based on the community in the Perhutani area of Poncokusumo is possible to be applied.